(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, we present a Extreme possibility estimation to analyze examine the strong ATR doses can work hypothalamic GnRH inhabiting life unlocks patterns in a style that is exactly the same as seen in the LH secretion. In presentation, inflammatory hormone levels are likely to work in response to GnRH. Finally, we decide that a computational model is based on the submission portion and we result with the medical refort . This paper will be very useful in the future for medical field.